(untitled) (Research, Society and Development, 2022)
Vitamin D is traditionally known for its role in regulating calcium homeostasis and consequently maintaining bone integrity and health. However, more recently, it has been observed that it has a series of previously unknown non-canonical functions, such as maintenance of immunity and intestinal mucosa integrity. Furthermore, it has been shown to be associated with the progression or perpetuation of several diseases since its serum concentration is reduced during the course of the conditions. Therefore, we sought to investigate, through a literature review, the usefulness of serum vitamin D measurement in dogs and cats as a prognostic factor for different diseases, as well as the possible therapeutic effect of supplementing this vitamin in the correction of those illnesses. Vitamin D is in fact deficient in gastroenteric diseases, such as protein-losing enteropathy, infectious diseases, such as canine leishmaniasis, heart and kidney disease, among others. However, it is necessary to understand more properly about the physiological role of vitamin D in health, so that we can also understand it in disease. There are also too few data reports supporting supplementing this vitamin as main or adjuvant therapy in the treatment of any disease, but evidence points to the usefulness of vitamin D serum measurement as a prognostic predictor for dogs and cats.